Biodiversity and ecology of dragonfly larvae in the plain zone of the Central Caucasus - Kozminov Sergey; Krapivina Elena; Paritov Anzor; Sabanova Raisa; Khandokhov Tahir (BIO Web of Conferences)
The paper presents the results of the analysis of the distribution and ecology of dragonfly larvae in the plain zone of the Central Caucasus. The results of differentiation of the distribution of species composition and communities from the factors of aquatic ecosystems and their biotopes, natural food supply and vegetation are substantiated. The conditions (complexes) of abiotic and biotic environmental factors that determine the development of certain taxa of dragonflies, the composition of populations and communities are established. It is determined that the altitudinal-belt vector determines natural filtration processes, water mass exchange and characterizes plain water bodies with polysaprobic and mesosaprobic biotopes with a high content of organic matter. It was revealed that environmental factors determine the natural food supply of larvae, the full cycle of preimaginal development, the beginning and end of metamorphosis, hatching and reproduction of adults. It has been established that the composition of populations depends on temperature dynamics, the quantitative and qualitative composition of the natural food supply, and the physical and chemical composition of water. It was proposed to use dragonflies as bioindicators and organize background monitoring of aquatic ecosystems in specific habitats and the degree of pollution with organic matter.